Revisão taxonômica de Dipsas Laurentis, 1768 (Serpentes, Colubridae) de ocorrência na Mata Atlântica - Porto, Marcovan (1993)
The taxonomic revision of Dipsas from the Atlantic forest Is given based on morphological and hemipennial data as well as on geographical distribution. The involved species are: Dipsas albifrons (Sauvage, 1884), D. catesby (Sentzen, 1796), D. incerta (Jan, 1863), D. petersi Hoge & Romano, 1975, D. neivai Amaral, 1923 and Dipsas sp. The principal results obtained are: 1) Description of a new species of the indica group with occurrence in the southeast Brazil associated to semidecidual and decidual forests; 2) the realocation of D. indica bucephala (Shaw, 1802) in the sinonimy of D. indica indica Laurenti, 1768; 3) the elevation of D. indica petersi Hoge & Romano, 1975 to the species levei; 4) the redescription of Dipsas albifrons, D. catesby, D. incerta, D. petersi e D. neivai, with the extension of knowledge on meristic characters variation and on geographical distribution of the involved species; 5) confirmation of the presence of D. catesby (Sentzen, 1796) in the Atlantic forest; and 6) acquisition of knowledge on reproductive period of Dipsas albifrons, D. incerta, D. petersi e D. neivai e Dipsas sp., that revealed to be aseasonal, oviparous, and that the groups of eggs in oviducts range between 1-9.